Factors Effecting Organizational Engagement of Employees at ABC Company Limited - Phowong, Dechawat; Phoemphian, Thanasit; Suankul, Uthai (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This research aims to study factors affecting organizational engagement of employees and to find guidelines for developing organizational engagement of employees. The research was conducted in two phases, namely phase 1 which was divided into two parts: Part 1 was qualitative Research. The researcher utilized group interviews with group of managers scrutinized from the literature review to find factors influencing organizational engagement of employee. Part 2 was quantitative research. The sample group included employees of ABC company limited. The research tool used was a questionnaire with a reliability at 0.925. Statistical use to analyze data comprised data percentage, mean, standard deviation, Pearson correlation and Multiple regression to confirm factors influencing organizational engagement of employees. Phase 2 was qualitative enquiry conducted to explore guidelines for developing organizational engagement of employees. The research findings indicates that the level of organizational engagement of employees at ABC company limited was at high level. The aspect of organization environmental had the greatest impact on organizational engagement of employees, followed by job characteristics. Factors aspect of human resource management systems and personal and social aspect within the organization did not significantly influence organizational engagement of employees. The data from the research were used as a guideline for the development of human resource management based on various factors, as follows: 1. Organizational environment: performed organizational values; 2. On job characteristics: defined decision-making authority at each level in the work manual; 3. On human resource management systems: performed plans for adjusting salary structures for both existing and new employees; 4. On personal and social aspect: performed plans for building employees’ relationships.